Retrospective analysis of ferric sulfate and sodium hypochlorite pulpotomy procedures in primary molars - Hayri Akman; Koray Surme (Tabriz University of Medical Sciences, 2023)
Background. Pulpotomy is a vital pulp treatment procedure frequently used in primary molars to preserve pulp vitality and function until tooth exfoliation. There is currently no pulp medicament with all the features of the ideal pulpotomy material. The present study compared the radiographic success of sodium hypochlorite with ferric sulfate (FS) when used for pulpotomy in primary molars. Methods. A retrospective analysis was performed to evaluate the success rates of primary molars pulpotomized using sodium hypochlorite or FS according to radiographic findings. Healthy 4‒10-year-old children who had pulpotomy procedures on primary molars between 2018 and 2021 at the pediatric dental clinic and had a control radiograph at least 12 months later were enrolled in the study. The chi-squared test was used to determine the differences in success between these two materials. Results. A total of 142 teeth, including 85 (59.9%) first primary molars and 57 (40.1%) second primary molars, in 98 healthy children were evaluated. The mean follow-up period of the teeth included in the study was 585.1±249.4 days. Radiographic success rates for NaOCl and FS groups were 73.8% and 71.0%, respectively, with no statistically significant difference (P>0.05). Internal root resorption (IRR) was the most common cause of radiographic failure in both groups. Conclusion. Radiographic success rates of both materials were similar, and using these materials in primary molar pulpotomy procedures can be recommended in clinical practice.